The pond snail Lymnaea stagnalis - Kuroda, Reiko (EvoDevo, 2020)
The freshwater snail Lymnaea stagnalis has a long research history, but only relatively recently has it emerged as an attractive model organism to study molecular mechanisms in the areas of developmental biology and translational medicine such as learning/memory and neurodegenerative diseases. The species has the advantage of being a hermaphrodite and can both cross- and self-mate, which greatly facilitates genetic approaches. The establishment of body-handedness, or chiromorphogenesis, is a major topic of study, since chirality is evident in the shell coiling. Chirality is maternally inherited, and only recently a gene-editing approach identified the actin-related gene Lsdia1 as the key handedness determinant. This short article reviews the natural habitat, life cycle, major research questions and interests, and experimental approaches.